THE INFLUENCE OF LEVERAGE AND SALES GROWTH ON EARNINGS MANAGEMENT (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the relationship between the effect of proxied leverage with Debt to Equity Ratio (DER), Sales Growth (SG) on Earnings Management (EM). The research method uses explanatory. The research population was 20 BUMN companies listed on the Indonesia Stock Exchange in 2015-2018. The sampling technique used was purposive sampling technique based on the sampling criteria of 8 companies with 32 annual observations of financial statement observations. The analysis using panel data regression was processed by the Eviews 10. The results show that DER and SG have a significant effect on EM. The suitability of theoretical and empirical models shows a fairly strong model.